Analisis Implementasi Kebijakan Program Pengendalian Resistensi Antimikroba (PPRA) - Rukmini Rukmini; Selma Siahaan; Ida Diana Sari (Buletin Penelitian Sistem Kesehatan, 2019)
Antimicrobial resistance has become a problem in Indonesia. The Ministry of Health has established a policy ofAntimicrobial Resistance (AMR) Control Program in hospitals to resolve the issue. A qualitative case study was conducted at Dr. RSUP Wahidin Sudirohusodo hospital, Makassar in 2018 to analyze the implementation of AMR control program. The data were collected through in-depth interviews and analyzed descriptively. The study showed that policy AMR control program has not be carefully implemented. The function of AMR control program team is to make policies and guidelines for antibiotic use, to make surveillance of germ patterns and antibiotic sensitivity, clinical audits of antibiotic use, to conduct studies/research and to make evaluation that is reported to the Hospital Director. However, this AMR control program has not been optimally implemented due to many challenges such as lack of budget, lack of commitment and internal coordination between the AMR control program team members. Implementation of AMR control program in this hosptal management is not optimal. The Program dissemination and AMR team activities were not evenly distributed. High workload, inadequate infrastructure and antibiotic resistance issues of the referred patients. As a conclusion AMRcontrol program policy in RSUP. Wahidin Sudirohusodo, Makassar, has not been properly disseminated and implemented. Coordination, dissemination and discussion forums on PPRA policies internally and externally with cross-sectoral hospitals are needed to improve antimicrobial resistance control commitment.